ANTIHISTAMINE AS AN ADJUNCTIVE TREATMENT IN ACNE VULGARIS: A SYSTEMATIC REVIEW AND META-ANALYSIS - Denny Saptono Fahrurodzi; Kunlawat Thadanipon; Sasivimol Rattanasiri; Ammarin Thakkinstian (Asian Journal of Social and Humanities, 2023)
Approximately one-tenth of the global population suffer from acne vulgaris, which is a skin disease with considerable psychological impact. Recently, antihistamines have been used in the treatment of acne. However, their overall treatment effects for this indication remain unclear. This systematic review and meta-analysis aim to evaluate the clinical efficacy and safety of the antihistamines in the treatment of acne vulgaris. The following databases were searched: PubMed, Scopus, Embase, Cochrane Central Register of Controlled Clinical Trials, and Google Scholar. We included the randomized controlled trials on acne vulgaris patients which compared any H1- antihistamine drug in combination with other medications to placebo, no treatment, or other medications, with acne lesion (non-inflammatory and inflammatory) counts, acne severity score, patient satisfaction, acne flare, or adverse events as an outcome of interest. Six studies contributing to 388 patients were included, involving two H1 antihistamines (i.e., levocetrizine and desloratadine), isotretinoin, azithromycin, and topical azelaic acid cream. From the network meta–analysis, levocetirizine+isotretinoin was better than the isotretinoin alone in the inflammatory lesion count, but not in the non-inflammatory lesion count. The desloratadine+isotretinoin retained the best balance in terms of non-inflammatory lesion count, inflammatory lesion count, acne flare, and mucocutaneous adverse events. The desloratadine+isotretinoin and levocetirizine+isotretinoin were considered safe.